Refinamento químico-mineralógico de perfil laterito-bauxítico de Juruti-PA, Brasil - NEGRÃO, Leonardo Boiadeiro Ayres (2019)
Bauxites are the main raw materials of aluminum and refractory industry. Brazil currently stands as the fourth largest producer of this ore, also being the country that has its third largest reserves, of which 97% are in the Amazon region. The main restriction of the bauxite’s mining in Amazon region is the up to 20 m thickness overburden made of yellowish clays (Belterra Clay), besides the difficulty and costly of chemical and mineralogical quantification of bauxites, particularly of available alumina and reactive silica. This paper evaluates the use of the Rietveld refinement to address these deficiencies. For this purpose, 17 samples were selected from a bauxite ore and its clay overburden in Juruti, Brazil, studied previously by Cruz (2011) and published by Costa et al. (2014). After mesoscopic description, the samples were analyzed by X-ray diffraction, x-ray fluorescence and scan electron microscopy. Cluster analysis was used to arrange similar x-ray patterns in order to apply different refinement’s strategies for the distinct x-ray patterns types recognized. The bauxite bearing regolith, with 23 m in depth, comprises a mottled horizon at the bottom with kaolinite, quartz and hematite; a bauxitic horizon consisting mainly of gibbsite with goethite, hematite and anatase in minor proportions; an iron crust with dominant hematite and goethite; a horizon with ferruginous nodules and clayey matrix composed by hematite, goethite, gibbsite and kaolinite; a horizon with bauxitic nodules and clayey matrix where gibbsite turns into the dominant phase, and; a clay cover horizon comprising mainly to kaolinite and goethite, with gibbsite, anatase and quartz in minor proportions. The Rietveld refinement was highly influenced by the material crystallinity, by the lack of proper crystallography structures and by the amorphous content, with seams to consist mainly in kaolinites. The refinement evaluation was made by the goodness-of-fit, the R factor values, the fitting of the calculated profile and the reproducibility of the method and appear to be satisfactory, proving that the Rietveld method is applicable and, besides its limitations in the mineral quantification of the laterite-bauxitic profile of Juruti-PA, is feasible to characterize and quantify bauxite due to its convenience and speed, crucial to discover new reserves.